PENGARUH POLA ASUH KELUARGA TERHADAP PERILAKU PESERTA DIDIK DI MI MA’ARIF NU BRUNOSARI PURWOREJO JAWA TENGAH - Siti Anisatun Nafi'ah; Ita Hesti Ernawati (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2020)
Family care patterns have an important role in shaping children's behavior. Pla foster children from childhood describe the behavior of children when children are adults. Good parenting will produce good child behavior. In this study the authors found a student who has a different behavior with his friends. Therefore the author wants to examine the effect of family parenting on children's behavior. This research uses qualitative research. Data analysis techniques used in this study with descriptive research, a researcher conducts the analysis only up to the description level, namely analyzing and presenting facts systematically so that it can be more easily understood and concluded. Based on the results of the study the authors found that students are very difficult to regulate in the learning process in class. Students when learning only play and draw. The student is difficult to manage not only during class hours, at the time of the ceremony he also can not be silent. Based on the results of educator interviews with his family that the child is only raised by a grandmother. Parents of students have divorced.